Laparoscopic therapy for Mirizzi syndrome: A case report with review of literature - Raj, Mounish; Joshi, Abhijit (Indian Journal of Case Reports, 2024)
Mirizzi syndrome (MS) is a rare entity and is due to extrinsic biliary compression. It is a rare complication of cholecystitis and chronic cholelithiasis. The impacted calculi at the infundibulum of the gall bladder or cystic duct lead to compression of the adjacent biliary structures, resulting in total or subtotal obstruction of the common hepatic duct (CHD). This leads to liver dysfunction. We, herein, present one such case of a 50-year-old female patient who was diagnosed to have MS. During surgery, at laparoscopy, she was unexpectedly also found to have a cholecysto-duodenal fistula. Both conditions were successfully treated laparoscopically.